Identifikasi Keragaman Genetik Gen Reseptor Hormon Pertumbuhan (GHR|Alu I) pada Sapi Bali - Zulkharnaim Zulkharnaim; . Zakaria; R R Noor (Media Peternakan, 2010)
Growth hormone receptor (GHR) is one factor affecting animal growth. GHR is required by growth hormone (GH) to carry out its effects on target tissues. The objective of the study was to estimate genetic diversity of the GHR|AluI gene in bali, limousin, simmental and pesisir cattle. Genotyping was performed on 248 animals, including 162 bali, 21 limousin, 17 simmental and 48 pesisir. Single nucleotide polymorphisms (SNP) had been found in exon 10, coding for the cytoplasmic domain of GHR, which was located at position 81 bp (A/G) induced amino acid substitutions Ser/Gly. Genotype frequencies of bali cattle AA (0.988), GG (0.006) and AG (0.006) were evidenced for the GHR AluI monomorphism, but mostly different from limousin GG (0.667), AA (0.238) and AG (0.095), simmental AG (0.529), GG (0.471) and AA (0.000), pesisir AA (0.604), GG (0.375) and AG (0.021) were the evidence of polymorphism. Homozigosity (monomorphism) in bali cattle might be affected by adaptability in extreme environmental conditions such as poor nutrition and improper management practices. It also could be affected by natural selection and phenotype plasticity phenomena.